2020
DOI: 10.21203/rs.3.rs-38707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the Glass Half-Full or Half-Empty? A Content Analysis of Adolescent Sexual and Reproductive Health in Global Financing Facility Country Plans

Abstract: Abstract Background: The Global Financing Facility (GFF) offers an opportunity to close the financing gap that holds back gains in women, children’s and adolescent health is recognised as a key priority by the GFF leadership. However, very little work exists examining GFF practice. As momentum builds for the GFF, we examine the initial efforts of the GFF in addressing adolescent health.Methods: We undertook a content analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A growing body of work has begun to independently examine the investment of the GFF [ 12–16 ]. George and colleagues examined GFF documents for 11 countries regarding adolescent sexual and reproductive health, revealing differences between countries and between the two main GFF country policy documents available, the investment cases (ICs) and project appraisal documents (PADs) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of work has begun to independently examine the investment of the GFF [ 12–16 ]. George and colleagues examined GFF documents for 11 countries regarding adolescent sexual and reproductive health, revealing differences between countries and between the two main GFF country policy documents available, the investment cases (ICs) and project appraisal documents (PADs) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, data is only useful if it is used to inform policies and programmes. In many places, the growing body of abundant epidemiologic information and findings from social and behavioural studies, do not feed into policy formulation, programme design or-as George et al have shown-in investment case development [22]. This must change.…”
Section: Introductionmentioning
confidence: 99%